Competent to provide compassionate care? A critical discourse analysis of accreditation standards. Issue 4 (20th December 2020) - Chen, Amanda Y.; Kuper, Ayelet; Whitehead, Cynthia R.
Abstract: Background: Medical school accreditation is recognised internationally as an important quality control process for programmes that lead to the Medical Doctor (MD) degree. Accreditation standards govern the accreditation process which in turn drives educational objectives. Given the power of these standards to shape what becomes valued in the curricula, it is therefore imperative to ensure that core values and ideals of the profession are meaningfully incorporated. As the provision of compassionate care has long been a central medical value, this value should be clearly articulated in MD programme accreditation standards. Methods: We conducted a Critical Discourse Analysis of compassionate care within Undergraduate Medical Education (UME) Accreditation Standards governing North American medical schools since 1957. We explored how and to what extent the written language of the accreditation standards incorporated compassionate care. Results: References to compassionate care in the UME Accreditation Standards were few and far between. Historically, a statement of 'The Objectives of Undergraduate Medical Education' published by the Association of American Medical Colleges (AAMC) was referenced for the first and only time in the 1957 standards, describing the development of attributes such as the provision of compassionate care as a basic objective of UME. Thereafter, there was infrequent mention of this value. Terms that could potentially incorporate aspects of compassionate care were identified, yet these were explicated in ways that limited connection to compassion. Instead, the term 'care' has increasingly been used instrumentally (ie acute care, chronic care). Conclusion: The relative absence of language pertaining to compassionate care in accreditation standards is troubling as compassion is integral to good medical care. This absence is particularly important to attend to in the current era of competency‐based training where we must be explicit about all important curricular objectives lest essential values and practices be unintentionally lost. Abstract : Noting that fundamental values not explicitly described in formal accreditation standards risk becoming lost in education practices, Chen et al. identify a troubling absence of compassionate care reflected in current standards.